2022
DOI: 10.4102/sajpsychiatry.v28i0.1547
|View full text |Cite
|
Sign up to set email alerts
|

From ideation to attempt: A study of suicidality and its correlates amongst patients with schizophrenia in a resource-poor country

Abstract: This study assessed the prevalence and pattern of suicidality and its relationship with certain sociodemographic and clinical variables.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3

Citation Types

2
1
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
4

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(3 citation statements)
references
References 44 publications
2
1
0
Order By: Relevance
“…Previous study indicated that the more patients spent on their illness monthly, the worse quality of life of informal caregivers, in particular the population with low income and lack of medical security. 23 This result was similar to our study. It is well-known that PLWHA require lifelong therapy with combinations of antiretroviral drugs, necessitating substantial economic resources.…”
Section: Discussionsupporting
confidence: 93%
“…Previous study indicated that the more patients spent on their illness monthly, the worse quality of life of informal caregivers, in particular the population with low income and lack of medical security. 23 This result was similar to our study. It is well-known that PLWHA require lifelong therapy with combinations of antiretroviral drugs, necessitating substantial economic resources.…”
Section: Discussionsupporting
confidence: 93%
“…Studies from populations in sub–Saharan Africa on suicidal attempts in persons with schizophrenia are scarce. A study in Ethiopia found an SB prevalence of 30% ( 31 ), which is closely similar to our study (32%); however, in Nigeria, the prevalence of SB was higher than in our study at 43% ( 32 ). This higher prevalence was attributed to the very high levels of stigma for schizophrenia and psychotic disorders found in Nigeria ( 33 ).…”
Section: Discussionsupporting
confidence: 88%
“…Additionally, high suicide attempts was found to be associated with increased suicidal ideation in people with SZ, similar to a previous study [ 68 ]. Suicide is a continuous process, and more suicide attempts may lead to more suicides [ 69 ]. Of interest, the results of the moderating effects show that this relationship weakened with increases in the RBANS-Visuospatial, Language, Attention, and IRI-PD scores.…”
Section: Discussionmentioning
confidence: 99%